Bubble growth dynamics including gravitational and electric field effects - Di Bari, Sergio (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2011)
In the present work the hydrodynamics of adiabatic gas bubble growth from a submerged orifice is investigated with the view of elucidating the interdependence of the bubble shape and the pressure field during growth and departure for different test conditions. The influence of both gravitational and electric fields around a single isolated bubble during its growth have been investigated experimentally with the aid of high speed photography and detailed image processing. To facilitate this, an uncomphcated yet versatile experimental apparatus has been commissioned which can simultaneously measure the internal gas pressure and the shape of the bubble during its lifetime. The design of the experimental rig allowed the user to modify the bubble growth conditions such as the flow rate and the orifice size. In addition to this, the effect of a uniform electric field was also studied by applying a high voltage potential across the region within which the bubbles grew.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin